Determinants of Bank Profitability in Turkey: An Empirical Analysis on Types of Banking from 2002 to 2012 - Eşref Savaş Başçi; Öznur Sakinç (Turkish Economic Review, 2014)
In this study, we investigate the determinants of banking profitability related to their financial statements. One of the major aim of financial systems is to make stability over the financial companies. Well known financial companies are Banks. If Banks make more profitable works, it can provide better effect to sector as an efficiency. The profitability of banks are more important for financial systems. Because of a lot of factors may affect to the banks as a widely way. Some researchers may emphasize banks earnings how it can improve which internal and external forces. Main studies are focused on banks financial statements. Therefore it is important how can we analyse their financial statements for evaluating profitability. With this current emphasis on financial statements are very important to both managing future and making new decision to guide. In Turkey, during from 2002 to 2012 period, bank's profitability approaches has been changed to new phenomenon. Because of regulative decisions and competitive market has to change profitability of banking sectors. Therefore banking sector profitability are substantial for Turkey which to understand the determinants of all types of banks. On the other hand, financial atmosphere give priority to above changes for evaluating their performances. Therefore many studies were analysed profitability with various methods like ratio analyses, predicting regression model, simulation methods and etc. Some learning from expert's experiences are rely on use of panel comparison with others about same historical infrastructure. In this study we examines types of banks as follows: 3 banks in state-owned banks, 12 banks in Private banks, 6 banks in foreign banks which has a branches in Turkey. In total 21 banks and 3 types analyses with cross-sectional panel data method during the from 2002 to 2012 period. In this study, we obtained data from Income Statements and Balance Sheets. As a result of panel data regression are statistically significant which Interest Income / Total Income and Consumer Loan/Total Loan are highly important to estimate ROE than estimating ROA.
Keywords: P17; P34; P52; 330; Determinants of Banking Sector; Profitability; Turkey Banking Sector